2008
DOI: 10.1007/s10342-008-0235-5
|View full text |Cite
|
Sign up to set email alerts
|

Canopy composition as a measure to identify patterns of nutrient input in a mixed European beech and Norway spruce forest in central Europe

Abstract: The influence of canopy composition on litterfall and throughfall was investigated in a mixed spruce beech forest in central Germany. We hypothesised that different parts of the mixed canopy created distinct patterns of element inputs via litterfall and throughfall. The investigation was carried out in two plots, representing the most contrasting cases of mixed forests: a stand greatly dominated by spruce (SDP) and a stand greatly dominated by beech (BDP). The canopies of the two plots were classified in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
(72 reference statements)
0
18
0
Order By: Relevance
“…Even though our estimated throughfall flux of Ca 2+ was rather low in comparison to other findings in the literature, Berger et al (2009b) found similar low values. The estimated throughfall flux of K + , on the other hand, was rather high in comparison to values in Parker (1983), Thimonier et al (2005) and Hojjati et al (2009). We cannot exclude the possibility that we over-or underestimated throughfall fluxes for some of the nutrients.…”
Section: Estimation Of Annual Fluxesmentioning
confidence: 78%
See 1 more Smart Citation
“…Even though our estimated throughfall flux of Ca 2+ was rather low in comparison to other findings in the literature, Berger et al (2009b) found similar low values. The estimated throughfall flux of K + , on the other hand, was rather high in comparison to values in Parker (1983), Thimonier et al (2005) and Hojjati et al (2009). We cannot exclude the possibility that we over-or underestimated throughfall fluxes for some of the nutrients.…”
Section: Estimation Of Annual Fluxesmentioning
confidence: 78%
“…Tree species with different foliage properties exhibit different patterns of throughfall water and ion fluxes (Beier et al 1993;Hansen 1995;Raat et al 2002;Whelan et al 1998). Furthermore, as dry deposition is also a function of foliage properties (Lovett 1994), it may cause species-related differences (Hojjati et al 2009;Rothe et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors, which were found to contribute to differences in deciduous tree species, are, e.g., canopy interception (throughfall), canopy-precipitation interaction, stem flow, rooting patterns, root litter (Falkengren-Grerup, 1989;Nordén, 1991;Dijkstra and Smits, 2002;Dijkstra, 2003;Meinen, 2009). Horizontal ranges of litter fall have been studied (Ferrari and Sugita, 1996;Staelens et al, 2003Staelens et al, , 2004, but horizontal ranges of tree effects on soils properties have been investigated less (Zinke, 1962;Rothe, 1997;Rothe et al, 2002;Hojjati et al, 2009). Guckland et al (2009) analyzed mixed deciduous forests on a plot basis indicating differences in species-specific tree-soil interactions, as well as clay content in the soil being an important covariable.…”
Section: Introductionmentioning
confidence: 96%
“…In addition an external N via throughfall under the spruce canopy can suppress CO 2 formation (Berg and Matzner 1997). Hojjati et al (2009) reported higher fluxes of inorganic nitrogen in throughfall under the canopy of spruce in the same experimental area.…”
Section: Discussionmentioning
confidence: 96%